Pain scores among ED patients: correlation with desire for pain medication - Marco, Catherine A.; McGervey, Megan; Gekonde, Joan; Martin, Caitlin (Translation: The University of Toledo Journal of Medical Sciences, 2014)
Introduction: Pain has been identified as the most common reason for Emergency Department (ED) visits. The verbal numeric rating pain scale (VNRS) is commonly used to assess pain in the ED. This study was undertaken to determine whether VNRS pain scores correlate with desire for pain medication among ED patients. Methods: In this prospective survey study, eligible patients included Emergency Department patients over 18 with painful conditions. The primary outcome measures included self-reported VNRS, ED diagnosis, number of ED visits and number of ED admissions within the past year, and the self-reported desire for pain medication. Results: Among 482 participants in 2012, the median triage pain score was 8 (IQR 6-10); the most frequently occurring score was 10. Overall, there were significant differences in pain scores with patient desire for analgesics. 67% reported desire for pain medications. Patients who did not want pain medications had significantly lower pain scores (median 6; IQR 4-8) compared to those who wanted medication (median 8; IQR 7-10) (p<0.001) and compared to those who were ambivalent about medication (median 7; IQR 6-10) (p=0.01). There was no association between desire for pain medication and demographics including age, gender, race, or insurance status. Conclusions: ED patients who did not desire pain medication had significantly lower pain scores than patients who desired pain medication. Pain scores usually effectively predicted which patients desired pain medications. Desire for pain medication was not associated with age, gender, race, or insurance status.